A Liouville comparison principle for solutions of quasilinear singular parabolic second-order partial differential inequalities - Kurta, V.V. (Доповіді НАН України, 2012)
The purpose of this work is to obtain a Liouville comparison principle for entire weak solutions (u, v) of quasilinear singular parabolic second-order partial differential inequalities. Встановлюється принцип порiвнювання Лiувiлля для цiлих, слабких розв’язкiв (u, v) квазiлiнiйних, сингулярних, параболiчних нерiвностей другого порядку в частинних похiдних. Устанавливается принцип сравнения Лиувилля для целых, слабых решений (u, v) квазилинейных, сингулярных, параболических неравенств второго порядка в частных производных.